Economic evaluation of air quality improvements in Klang Valley, Malaysia : validity and reliability of contingent valuation method - Rafia, Afroz (CESER Publications, 2004)
Malaysia has enjoyed one of the least polluted urban environments in Asia. The goal of achieving industrial country status by the year 2020, and the associated rapid economic growth has started to impose costs in terms of industrial pollution and degradation of urban environment. This research employed contingent valuation method (CVM) to estimate the willingness to pay of the respondents to improve the air quality in Klang Valley. The study evaluated the validity and reliability of contingent valuation method. This was done through split and paired sample surveys using three different question formats i.e. open ended (OE), dichotomous choice (DC) and payment card (PC).